Academic inbreeding and choice of strategic research approaches - Horta, H. (2022)
Academic inbreeding is a phenomenon that has been studied mostly from the standpoint of its association with research productivity. The focus has been on knowledge creation outputs and outcomes, while little to no attention has been given to the association of academic inbreeding with knowledge creation strategies and processes in academia. This article focusses on the latter, confirming that academic inbreeding is detrimental to the research aspirations, innovativeness, risk‐taking, and multidisciplinarity engagement of academics' research agendas, as predicted by literature. These findings, based on a sample of more than 7000 academics from all fields of knowledge, working in more than 140 countries, do not find a greater influence of the PhD mentor on the strategic research agendas of homegrown academics as the literature would expect. The findings also underline critical differences between homegrown academics and silver‐corded academics, stressing that the latter category of academics should not be considered as part of the academic inbreeding process (which concept rests on immobility), but rather understood as a category of limited institutional mobility that deserves further study.